Crystal Chemistry of Three Volcanic K-rich Nepheline Samples From Oldoinyo Lengai, Tanzania and Mount Nyiragongo, Eastern Congo, Africa - Antao, Sytle M.; Nicholls, James W. (Frontiers in Earth Science, 2018)
Natural nepheline (Nph) samples are intermediate members of solid solutions that extend from the pure Na end-member Na[AlSiO4] to the pure K end-member K[AlSiO4] (= kalsilite, Kls). We examined two volcanic nepheline (ideally, K2Na6[Al8Si8O32] or Nph0.75Kls0.25) samples from Oldoinyo Lengai, Tanzania (samples 1 and 2) and a third sample 3 from Mount Nyiragongo, Eastern Congo. The crystal structure of these three samples was obtained using synchrotron high-resolution powder X-ray diffraction (HRPXRD) data and Rietveld structure refinements in space group P63. Satellite reflections were not observed in these samples. The EPMA composition of sample 1 is K1.50Na0.19Ca0.070.23Σ2(Na)6[Si8.35Al7.48Fe0.18]Σ16.00O32. The A site contains 0.23 vacancies () with some Na and Ca atoms, whereas the B site is completely filled with only Na atoms. From the EPMA formula, K(sof) = 0.844 and Na(sof) = 1.0. The refinement unit-cell parameters are a = 10.00247(1), c = 8.38396(1) Å, V = 726.431(1) Å3; K(sof) = 0.779(2) and Na(sof) = 0.988(2). The composition of sample 2 is K1.670.33Σ2(Na5.76K0.174Ca0.06)Σ6[Si8.44Al7.37Fe0.20]Σ16.01O32, so K(sof) = 0.835 and Na(sof) = 1.030. Sample 2 has a = 10.01769(2), c = 8.39586(2) Å, V = 729.678(1) Å3, K(sof) = 0.812(2), and Na(sof) = 0.995(2). Sample 3 is a three-phase (3a, 3b, 3c) intergrowth with an average formula of {K1.770.23}2(Na4.30K1.51Ca0.19)Σ6[Si8.13Al7.76Fe0.11]Σ16.00O32, K(sof) = 0.887, and Na(sof) = 1.208. A large amount of K and Ca atoms occur in the B site. Based on the weight percentages and sofs of the three phases, the Rietveld refinement gives an average K(sof) = 0.859 and Na(sof) = 1.145. The average <T-O> distances indicate a high degree of Al-Si disorder in samples 1, 2, and phase 3b. These African samples extend natural nepheline solid solutions to about Nph0.55Kls0.45. The average <Na-O> distance increases linearly with Na(sof) and V across nepheline solid solutions because K atoms enter the Na site. K-rich nepheline seems to always contain vacancies in the A site.